The ultrastructure of spermiogenesis and spermatozoa in Diplomystes mesembrinus - Quagio-Grassiotto, I; Oliveira, C.; Gosztonyi, A. E. (Academic Press Ltd, 2001)
Spermiogenesis in Diplomystes mesembrinus, one of the most primitive species from the Siluriformes, occurs in cysts. Differentiation of spermatids is characterized by chromatin compaction, flagellum development, nuclear fossa formation, rotation of the nucleus, and excess cytoplasm elimination. The spermatozoon head is round, the nucleus contains highly condensed chromatin clusters, the midpiece is short, the axoneme shows a 9 + 2 pattern with two discrete lateral projections, and the acrosome is absent. The nuclear fossa penetrates deeply into the nucleus, including the centriolar complex and the start of the axoneme. The single large C-shaped mitochondrion sur rounds the: initial segment of the axoneme. The structural features of D. mesembrinus spermatozoon are similar to the Clupeiformes. (C) 2001 the Fisheries Society of the British Isles.
Keywords: fish; spermatid; sperm; structure